Montelukast, A Selective Cysteinyl Leukotriene Receptor 1 Antagonist, Reduces Cerulein-Induced Pancreatic Injury in Rats - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2010)
Objectives: This study was designed to evaluate the protective effect of the cysteinyl leukotriene receptor antagonist montelukast against pancreatic injury during acute pancreatitis. Methods: Acute pancreatitis was induced in rats by 20-mu g/kg (intraperitoneal) cerulein given at 1-hour intervals within 4 hours. Montelukast was administered intraperitoneally at a dose of 10 mg/kg 15 minutes before the first cerulein injection. Six hours after the cerulein or saline injections, the animals were killed by decapitation. Blood samples were collected to analyze amylase, lipase, and the proinflammatory cytokines tumor necrosis factor alpha and interleukin 1 beta. Pancreas tissues were taken for the determination of tissue glutathione and malondialdehyde levels and Na+, K+ Yadenosine triphosphatase and myeloperoxidase activities. The extent of tissue injury was analyzed microscopically. Results: Acute pancreatitis caused significant decreases in tissue glutathione level and Na+, K+ Yadenosine triphosphatase activity, which were accompanied with significant increases in the pancreatic malondialdehyde level, myeloperoxidase activity, and plasma cytokine level. On the other hand, montelukast treatment reversed all these biochemical indices and histopathological alterations that were induced by cerulein. Conclusions: These results suggest that cysteinyl leukotrienes may be involved in the pathogenesis of acute pancreatitis and that the cysteinyl leukotriene receptor antagonist, montelukast, might be of therapeutic value for treatment of acute pancreatitis.
Keywords: pancreatitis; leukotriene; montelukast; cytokines; oxidative damage; N-ACETYLCYSTEINE; OXIDATIVE STRESS; ASCORBIC-ACID; EXPERIMENTAL COLITIS; BLOCKER MONTELUKAST; LUNG INJURY; GLUTATHIONE; INFLAMMATION; GENERATION; ACTIVATION